A novel RNAseq–assisted method for MHC class I genotyping in a non-model species applied to a lethal vaccination-induced alloimmune disease. (December 2016) - Demasius, Wiebke; Weikard, Rosemarie; Hadlich, Frieder; Buitkamp, Johannes; Kühn, Christa
Abstract Background MHC class I genotyping is essential for a wide range of biomedical, immunological and biodiversity applications. Whereas in human a comprehensive MHC class I allele catalogue is available, respective data in non-model species is scarce in spite of decades of research. Results Taking advantage of the new high-throughput RNA sequencing technology (RNAseq), we developed a novel RNAseq-assisted method (RAMHCIT) for MHC class I typing at nucleotide level. RAMHCIT is performed on white blood cells, which highly express MHC class I molecules enabling reliable discovery of new alleles and discrimination of closely related alleles due to the high coverage of alleles with reads. RAMHCIT is more comprehensive than previous methods, because no targeted PCR pre-amplification of MHC loci is necessary, which avoids preselection of alleles as usually encountered, when amplification with MHC class I primers is performed prior to sequencing. In addition to allele identification, RAMHCIT also enables quantification of MHC class I expression at allele level, which was remarkably consistent across individuals. Conclusions Successful application of RAMHCIT is demonstrated on a data set from cattle with different phenotype regarding a lethal, vaccination-induced alloimmune disease (bovine neonatal pancytopenia), for which MHC class I alleles had been postulated as causal agents.